Linked data for cultural heritage - Jones, Ed 1951-; Seikel, Michele (An ALCTS monograph, 2016)
With its roots in computer science, linked data is unfamiliar territory for many library cataloguers, but since the origins of MARC nearly 50 years ago, the value of machine-readable library records has only grown. Today linked data is essential for sharing library collections on the open web, especially the digital cultural heritage in the collections of libraries, archives, and museums.